Cellular hypomethylation is associated with impaired nitric oxide production by cultured human endothelial cells - Barroso, M. (2013)
Hyperhomocysteinemia (HHcy) is a risk factor for vascular disease, but the underlying mechanisms remain incompletely defined. Reduced bioavailability of nitric oxide (NO) is a principal manifestation of underlying endothelial dysfunction, which is an initial event in vascular disease. Inhibition of cellular methylation reactions by S-adenosylhomocysteine (AdoHcy), which accumulates during HHcy, has been suggested to contribute to vascular dysfunction. However, thus far, the effect of intracellular AdoHcy accumulation on NO bioavailability has not yet been fully substantiated by experimental evidence. The present study was carried out to evaluate whether disturbances in cellular methylation status affect NO production by cultured human endothelial cells. Here, we show that a hypomethylating environment, induced by the accumulation of AdoHcy, impairs NO production. Consistent with this finding, we observed decreased eNOS expression and activity, but, by contrast, enhanced NOS3 transcription. Taken together, our data support the existence of regulatory post-transcriptional mechanisms modulated by cellular methylation potential leading to impaired NO production by cultured human endothelial cells. As such, our conclusions may have implications for the HHcy-mediated reductions in NO bioavailability and endothelial dysfunction.